The effect of combined compression and tactile stimulation on ankle somatosensation in a lunar gravity lower limb load analog - Marchant, Ashleigh; Witchalls, Jeremy; Wallwork, Sarah B.; Ball, Nick; Waddington, Gordon (Frontiers in Physiology, 2025)
Ankle somatosensation appears to be negatively affected when in simulated hypogravity (gravity, 1 > g < 0). Developing countermeasures to reduce this negative effect is necessary for sensorimotor control as astronauts prepare to explore the Moon. Head-elevated supine lying has been found to be an effective method in simulating the physiological impact of hypogravity by reducing the weight-bearing capacity through the lower limbs. This study investigated whether wearing a combined compression sock with plantar textured sole (compression-tactile sock) is associated with enhanced somatosensory acuity of the lower limbs in a simulated hypogravity environment. Ankle somatosensory acuity was assessed on 55 healthy participants between the ages of 18 and 65 years (female subjects 28, male subjects 27; mean age 41 years ±14). The active movement extent discrimination assessment (AMEDA) was used to assess somatosensory acuity on participants’ non-dominant foot under four conditions: (1) upright standing in barefoot; (2) upright standing wearing compression-tactile socks; (3) simulated hypogravity (head-elevated supine position) in barefoot; and (4) simulated hypogravity (head-elevated supine position) wearing compression-tactile socks. Analysis was conducted for (i) the whole participant group, (ii) high (above-average) performers, (iii) medium (average) performers, and (iv) low (below average) performers. It was hypothesized that low performers would experience the greatest gains when wearing the sock, compared to those in barefoot. When assessing the group as a whole, AMEDA scores were significantly reduced in the simulated hypogravity (head-elevated supine) conditions when compared to upright standing conditions (p < 0.001; 3% decline when barefoot; 2.9% decline when wearing the socks). Wearing compression-tactile socks had no effect on AMEDA scores when compared to barefoot (p = 0.173). When analyzed by the performance group, somatosensory acuity was enhanced in the compression-tactile sock condition, when compared to barefoot (upright, p = 0.009, 4.7% increase; head-elevated supine, p = 0.022, 3% increase) in the low performers only. In the medium and high-performer groups, there was no difference between the compression-tactile sock conditions and barefoot conditions (p > 0.05 for all). Compression-tactile socks may be associated with enhanced somatosensory acuity in upright standing and simulated hypogravity for individuals with below-average somatosensory acuity. Further research is warranted to assess the effect of compression-tactile socks in an actual hypogravity environment to determine whether the compression-tactile socks can maintain one’s somatosensory acuity.